Lagringsbehov i form av vätgas/batteri/annat-lager för ett 100 % förnybart elsystem för Sverige - Storage need for achieving a 100 % renewable power system in Sweden, utilizing battery/hydrogen/ other technologies - Ekstedt, Elin; Gyllenstedt, Joel; Hjalmarsson Vangebo, Alexander; Wolfbrandt, Ebba (My University, 2026)
In the pursuit of a 100% renewable electricity system in the SE3 area in Sweden, a possible solution could be energy storages systems. Data such as todays production, consumption, costs and environmental impact were researched to be used in a linear optimisation model. By setting limitations, the model could compute an estimate of the total price for production and investment cost for different scenarios. This resulted in information of how a change in, for example, how the price of batteries could impact the investment in energy storage. By analyzing these scenarios a couple of assumptions could be made regarding to what approach would be most cost effective and achievable in terms of reaching a 100% renewable energy system in the SE3 area. The results show that a solution using a combination of batteries, hydrogen energy storage and pumped hydropower could be a good option for minimizing cost and environmental impact while stabilizing the grid and maximizing energy efficiency. By only using a single source of storage the results showed that batteries and pumped hydro would each cost more than 900 billion SEK compared to a combination which would cost less than 300 billion SEK. The model further showed that the price of pumped hydropower and batteries highly influences the optimal investment. A small price reduction would greatly increase the investment in these storages.
Keywords: energilagring, förnyelsebar energi, variationshantering, bränslecell, vätecell, batteri, pumpad vattenkraft, elnät, teknoekonomisk analys